2022
DOI: 10.3390/medicina58060783
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Experience of Emergency Appendectomy under the COVID-19 Pandemic in a Single Institution in South Korea

Abstract: Background and Objectives: The COVID-19 pandemic has brought serious changes in healthcare systems worldwide, some of which have affected patients who need emergency surgery. Acute appendicitis is the most common surgical disease requiring emergency surgery. This study was performed to determine how the COVID-19 pandemic has changed the treatment of patients with acute appendicitis in South Korea. Materials and Methods: We retrospectively reviewed a medical database that included patients who underwent surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Patients undergoing operative management for appendicitis during the pandemic were assessed to have poorer overall health, as determined by their significantly higher ASA scores. This was not identified in other studies, which all reported no significant difference between the pandemic and control cohort ASA scores [ 37 , 38 , 42 ]. There are a number of explanations why our findings differed from other studies; the studies were conducted in different countries with differing health care systems, and the ASA is a subjective measure.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Patients undergoing operative management for appendicitis during the pandemic were assessed to have poorer overall health, as determined by their significantly higher ASA scores. This was not identified in other studies, which all reported no significant difference between the pandemic and control cohort ASA scores [ 37 , 38 , 42 ]. There are a number of explanations why our findings differed from other studies; the studies were conducted in different countries with differing health care systems, and the ASA is a subjective measure.…”
Section: Discussioncontrasting
confidence: 54%
“…We believe the significant increase in complicated appendicitis can account for the significant increase in rates of caecectomy and intraoperative insertion of drains. Other studies that recorded rates of caecectomy during the pandemic did not identify a significant increase [ 37 – 39 ]. Only one of these studies identified a significant increase in the rates of complicated appendicitis during the pandemic, and all were conducted in Korea and therefore examined a different population and health system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our hospital was not a COVID-19-dedicated hospital, and the impact of COVID-19 on hospital capacity was minimal. However, 1 study found that the time spent in the emergency department before surgery was significantly longer in the pandemic group (519.11 ± 486.57 minutes vs. 705.27 ± 512.59 minutes, P < 0.001) [ 23 ]. In our study, the 30-day postoperative complication rates and severity were similar between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%